ANALISIS HUBUNGAN PELATIHAN PRODUK MAKANAN TERHADAP KEMAMPUAN KETERAMPILAN SISWA DI SMK ANANDA BEKASI - AGUS HERMAWAN; LIES MAISAROH (SMART Management Journal, 2021)
This study aims to determine and analyze the relationship between food product training and the ability of students' skills at SMK Ananda Bekasi. Education is a form of human effort in improving its quality as a human being that can be done individually or in groups, Ananda Bekasi Vocational School which has a Hospitality Accommodation major where in class IX they get training material for food product training. This study uses historical-secondary data of grades IX grade students for the period 2017-2019, obtained a total of 78 students, then the data was cleaned to be processed. After testing with SPSS 25.0 software, the mean value of the training variable (X) 338.67 and the ability skills (Y) 167.47, the normality of the data obtained were normally distributed, the linear regression test obtained a significance result of 0.012, where it was less than 0, 05 it can be concluded that the training variables and skills ability have a correlation, the simulltan test obtained a value of 0.284 with the conclusion that the results of a close relationship (simultaneous) is low between the training variables (X) and skills ability (Y) with partial tests found a positive relationship and coefficient of determination (R2) 8.1%.